Effects of resistance training on binge eating, body composition and blood variables in type II diabetics - Moisés Simão Santa Rosa de Sousa; Victor Manuel Machado dos Reis; Jefferson da Silva Novaes; Josenaldo Mendes de Sousa; Divaldo Martins de Souza (Universidade Estadual de Maringá, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36n1.18048 This study examined the effects of 12 weeks of resistance training (RT) on binge eating, body composition and blood variables and their correlations in 34 sedentary adults with type II diabetes. The participants aged 58.94 ± 10.66, had body weight of 71.62 ± 11.85 and BMI of 29.64 ± 4.27. Blood samples were collected for analysis of serum leptin, glucose, insulin, LDL, HDL, total cholesterol and triglyceride. The binge eating was assessed by the binge eating scale and the body composition by bioelectrical impedance. The training included three weekly sessions for 12 weeks, with three sets from 12 to 15 repetitions for the main muscle groups, and interval from 1 to 2 minutes between the sets. A significant decrease was found for the binge eating, body weight, BMI, fat percentage, and fat weight. As for the blood variables, there was a significant reduction in leptin; non-significant reductions in glucose, total cholesterol, LDL and triglycerides; as well a significant increase in HDL and non-significant increase in insulin. In conclusion the 12 weeks of RT proved to be enough to decrease the binge eating, to positively adjust the body composition and to modify the blood profile, demonstrating an association at a lower or higher level between these variables.